2011
DOI: 10.1038/sc.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a new compact catheter for men with neurogenic bladder dysfunction: a randomised, crossover and open-labelled study

Abstract: Study design: Self-catheterising males aged X18 years with spinal cord lesion and normal/impaired urethral sensation were enrolled in this comparative, randomised, crossover and open-labelled multicentre trial. Objectives: When possible, intermittent catheterisation is the preferred method of bladder emptying for neurogenic bladder dysfunction. Hydrophilic-coated catheters have improved safety and ease of use, and a new compact catheter for men has been developed to improve discretion. Methods: Participants se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…demographic and baseline characteristics were considered representative for the target population, and it was concluded that the study population was homogeneous. For instance, in contrast to a previously reported tolerability study [16], all patients had maintained urethra sensibility, which is considered essential for obtaining valid subjective evaluations of a catheter material. All comparisons used paired data with the subjects as their own controls, which further minimized the risk of confounding factors.…”
Section: Discussionmentioning
confidence: 93%
“…demographic and baseline characteristics were considered representative for the target population, and it was concluded that the study population was homogeneous. For instance, in contrast to a previously reported tolerability study [16], all patients had maintained urethra sensibility, which is considered essential for obtaining valid subjective evaluations of a catheter material. All comparisons used paired data with the subjects as their own controls, which further minimized the risk of confounding factors.…”
Section: Discussionmentioning
confidence: 93%
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
“…Five RCTs compared compact hydrophilic with standard hydrophilic catheters in terms of satisfaction and/or quality of life (Table 3a). 29,[31][32][33][34] Only one article demonstrated a significant increase in satisfaction reported from patients using a compact hydrophilic catheter, when compared with patients using a standard hydrophilic catheter. 34 Chartier-Kastler et al, 34 conducted a prospective randomized crossover study to compare compact with standard catheters in terms of quality of life.…”
Section: Patient's Satisfaction and Quality Of Lifementioning
confidence: 99%